Značenje i prednost proučavanja židovske Biblije na biblijskom hebrejskom jeziku - DaDon, Agnes Eva (Array, 2019)
In this article the authors analyse the importance of the study of the Old Testament in its original language, Biblical Hebrew. The first part of the article consists of a general introduction followed by the explanation of the main linguistic differences between Biblical and Modern Hebrew, as one of the factors contributing to the difficulty of understanding the Bible even for native Israelis. This part ends with a brief description of the first Modern Hebrew translation of the Bible and the intentions behind this translation, as presented by the translator and the publisher.The central part of this article discusses the following issues: the need of a translation of the Bible from Biblical Hebrew into modern spoken Hebrew, the importance of the Bible and the Biblical text, continues with a general introduction to translation, provides arguments in favour and against the translation of the text from Biblical Hebrew into Modern spoken Hebrew or other languages. The end of this part exposes the difficulties involved in Bible translation, providing examples of major problems in the translation of the Bible. In this context, the background of Torah translations into Aramaic is explained.Finally, in the conclusion, the authors give their recommendations for the school curriculum in Croatia, based on their experiences as teachers and parents. In their work, the authors use many sources from the rabbinical literature since the Talmudic time through the Middle Ages until modern times. Much of this literature is translated into Croatian from Hebrew and Aramaic for the first time by the authors.